Erthroplasia of queryat- A case report - Ghimire, RBK; Mathur, M (Journal of College of Medical Sciences-Nepal, 2012)
Erthroplassia of Queryat (EQ) is a rare squamous cell carcinoma in situ of the penis. It usually occurs on the glans penis and appears as a well-marginated erythematous velvety patch or plaque. Here, we present a case of Erthroplasia of Queryat (EQ). Journal of College of Medical Sciences-Nepal,2011,Vol-7,No-4, 67-69 DOI: http://dx.doi.org/10.3126/jcmsn.v7i4.6815